Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Square (TPSQ) Terhadap Kemampuan Penalaran Matematis Peserta Didik Kelas XI MIPA SMAN 3 Padang - RIZKI DARMANSYAH (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematicalvreasoning is one of the basicmabilities that every student must have in learninpg mathematics. However, the observationkresultsg obtained gindicate that the gmathematicallreasoning ability of students of class XI MIPA in SMA Negeri 3 Padang is can still bekimproved. The implementationpof learning is still centered on the teacher, so students tend to be more passivehin learning. One effort tomovercome this problem is to implementpthe ThinkhPair SquaremCooperative learningmmodel. The purpose of thismresearch is to describe whethert the mathematicalvreasoning ability of students who learn using CooperativebThink Pair Square Type models is better than students who learn to use conventionalclearning in class XI MIPA SMA Negeri 3 Padang. This type of research is a quasycexperiment with a Static GrouppDesign. Sampling was carriedo out by SimplevRandom Sampling technique. Data on mathematicalbreasoning ability were analyzed usingbt-test. Based on datamanalysis, it is found that ThinkpPair Square Cooperative learningbmodel influences the students' mathematicalmreasoning ability, so that theh mathematicaln reasonig abilityj of students whoh learn witha Cooperative gLearningbmodel Think gPair ySquare is better than dstudents who learn withb conventional blearningjin XI MIPA high school Negeri 3 Padang.Keywords---conventionalplearning, mathematicalpreasoning, Think PairpSquare Cooperativellearning model.